(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
The presented research paper deals with analytical method to determine the thermal conductivity of porous material (intumescent coating) where the main objective is to assess whether it is possible to treat the voids in intumescent coating as having a uniform diameter. Considering the nature of intumescent coating, the mechanisms of its fire retardant properties are expansion and heat absorption. A predictive model should therefore include prediction of expansion behaviour, energy and mass conservation based on both physical and chemical behaviour, and also thermal conductivity of the coating. A 3-D analytical model will be developed to determine the thermal conductivity of intumescent coating. Finite Element simulations using ABAQUS also will be performed to assess the influence of different pore size distributions. The results of this numerical study indicate that, given the same porosity, the overall thermal conductivity of the porous structure is very close to that with uniform distribution of pores of the dominant size. This strongly suggests that, given the difficulty of obtaining precise pore size distribution, it is reasonable to treat an intumescent coating as having a uniform distribution of pores of the same size.